Kegiatan KKN Virtual Mahasiswi STIBA Makassar Berbasis Al-Qur’an di Sumatera Utara - Kurnaemi Anita; Nuraeni Novira (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The purpose of the implementation of this KKN is to empower, foster, and increase the capacity of the local community. The method of implementing the KKN program begins by observing the condition of the community using SOAR analysis which then produces several programs including: (1) Seminar Al-Qur’an; (2) Tahfiz Harian; (3) Pengajaran Al-Qur’an Metode Dirosa; (4) Taklim Fikih Muslimah, dan (5) Poster Dakwah. All these programs are running well and smoothly, this is characterized by the continued program of coaching and teaching of the Qur'an even though the KKN has ended. As a result, there appears to be a change in the attitudes and behavior of more religious people, and the ability to read the Qur'an is getting better.